Monitoring tools of COMPASS experiment at CERN. Issue 8 (December 2015) - Bodlak, M; Frolov, V; Huber, S; Jary, V; Konorov, I; Levit, D; Novy, J; Salac, R; Tomsa, J; Virius, M
Abstract: This paper briefly introduces the data acquisition system of the COMPASS experiment and is mainly focused on the part that is responsible for the monitoring of the nodes in the whole newly developed data acquisition system of this experiment. The COMPASS is a high energy particle experiment with a fixed target located at the SPS of the CERN laboratory in Geneva, Switzerland. The hardware of the data acquisition system has been upgraded to use FPGA cards that are responsible for data multiplexing and event building. The software counterpart of the system includes several processes deployed in heterogenous network environment. There are two processes, namely Message Logger and Message Browser, taking care of monitoring. These tools handle messages generated by nodes in the system. While Message Logger collects and saves messages to the database, the Message Browser serves as a graphical interface over the database containing these messages. For better performance, certain database optimizations have been used. Lastly, results of performance tests are presented.